Scaffolding strategy and speaking skills development in the English teaching process: Estrategia de andamiaje y desarrollo de la expresión oral en el proceso de enseñanza del inglés (Papeles, 2025)
Introduction: The purpose of this review article is to provide readers with an overview of research made on the influence of the scaffolding strategy on the development of English speaking skills, including information such as its effectiveness in the English classroom and an account of the facets of this strategy that should be further developed. Method: Exploring two well-known open access databases: ERIC and Scilit, the authors collected thirteen articles published between 2020 and 2024. The review focuses on analyzing the effectiveness of scaffolding strategy in improving speaking skills in English, making emphasis on the types of scaffolding employed and their characteristics. Results and Discussion: The analysis of the articles is based on four main types of scaffolding: conceptual, procedural, strategic, and metacognitive. Conceptual scaffolding introduces learners to key pieces of information, procedural scaffolding refers to the assistance given regarding the utilization of tools for learning, strategic scaffolding refers to the employment of alternative procedures to reach an objective and finally, metacognitive scaffolding fosters self-regulation, reflection, and is supported by feedback. The selected studies have been labeled according to this classification, thus obtaining articles that included from one to multiple scaffolding types. Conclusions: This article demonstrates that scaffolding is a highly effective strategy for developing English learners’ speaking skills.
Keywords: Scaffolding strategy; speaking skills; English language acquisition